Line mixing in the nitric oxide R-branch near 5.2 μm at high pressures and temperatures: Measurements and empirical modeling using energy gap fitting. (December 2021) - Almodovar, Christopher A.; Su, Wey-Wey; Choudhary, Rishav; Shao, Jiankun; Strand, Christopher L.; Hanson, Ronald K.
Highlights: Development of a temperature-dependent line mixing model for nitric oxide near 5.2  μ m broadened by N 2 and Ar through energy gap fitting laws applied to experimental pressure broadening coefficients. High-pressure (up to 33 atm) and high-temperature (up to 802 K) measurements of the nitric oxide R-branch in N 2 compare favorably to the line mixing model. The nitric oxide line mixing model is applied to a two-wavelength temperature measurement strategy in high-pressure shock tube experiments at pressures up to 90 atm and temperatures up to 2500 K with relatively good agreement between measured and known temperatures. Abstract: Evidence of line mixing has been observed in the infrared spectra of many gaseous species at high densities or in the low absorbing windows between optical transitions. However, up to this point, no study exists of nitric oxide line mixing at pressures above atmosphere or temperatures several hundred degrees above room temperature. In this paper, the absorption spectrum of nitric oxide's R-branch broadened by N 2 near 5.2 microns is measured with an external cavity quantum cascade laser in a high-pressure, high-temperature optical static cell over a range of temperatures (294 – 802 K) and pressures (5 – 33 atm). An empirically-based, temperature-dependent line mixing model is built by assembling the impact relaxation matrix from fits (energy gap fitting laws) to pressure broadening coefficients that were measured in a previous study. The resulting line mixing model shows significant improvements over a simple superposition of Lorentzian line shapes when compared to the static cell measurements. To further demonstrate the model's use, the line mixing model is used to infer temperature in high-pressure (10 – 90 atm) shock tube experiments.